2007
DOI: 10.1016/j.jasms.2006.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of low energy CID and ECD fragmentation behavior of mono-oxidized thio-ether bonds in peptides

Abstract: Thio-ether bonds in the cysteinyl side chain of peptides, formed with the most commonly used cysteine blocking reagent iodoacetamide, after conversion to sulfoxide, releases a neutral fragment mass in a low-energy MS/MS experiment in the gas phase of the mass spectrometer [6]. In this study, we show that the neutral loss fragments produced from the mono-oxidized thio-ether bonds (sulfoxide) in peptides, formed by alkyl halide or double-bond containing cysteine blocking reagents are different under low-energy M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…H/D exchange experiments also confirmed that the neutral loss of CH 2 CHCONH 2 (CH 2 CHX=, where X= ϭ CONH 2 ) from these peptide ions occurred via a charge-remote cis-1,2 elimination reaction to yield the cysteine sulfenic acid-containing product ion (2), as shown in pathway B of Scheme 1. This is consistent with the mechanism recently proposed by Chowdhury et al for the neutral loss of 4-vinylpyridine from S-pyridylethyl cysteine sulfoxidecontaining°peptides° [8].…”
Section: Multistage Tandem Mass Spectrometry H/d Exchange Reactionssupporting
confidence: 92%
See 4 more Smart Citations
“…H/D exchange experiments also confirmed that the neutral loss of CH 2 CHCONH 2 (CH 2 CHX=, where X= ϭ CONH 2 ) from these peptide ions occurred via a charge-remote cis-1,2 elimination reaction to yield the cysteine sulfenic acid-containing product ion (2), as shown in pathway B of Scheme 1. This is consistent with the mechanism recently proposed by Chowdhury et al for the neutral loss of 4-vinylpyridine from S-pyridylethyl cysteine sulfoxidecontaining°peptides° [8].…”
Section: Multistage Tandem Mass Spectrometry H/d Exchange Reactionssupporting
confidence: 92%
“…Consistent with these observations, the mechanism responsible for the loss of XSOH from S-alkyl cysteine sulfoxide-containing peptides formed by reaction with iodoacetamide, where X ϭ CH 2 CONH 2 , has been proposed to occur via a "charge-remote" cis-1,2 elimination reaction involving transfer of the ␣-hydrogen atom to yield an acyclic dehydroalanine-containing product ion (1) (Scheme 1, pathway A) [6,7]. A similar cis-1,2 elimination mechanism, yielding a cysteine sulfenic acid-containing product ion (2) (Scheme 1, pathway B), has also been proposed for the loss of CH 2 CHX= from S-alkyl cysteine sulfoxide-containing peptides formed by reaction with acrylamide (X= ϭ CONH 2 ) [5] or vinylpyridine (X= ϭ C 5 H 4 N) [8], as well as for the loss of C 6 H 7 NO 2 from S-alkyl cysteine sulfoxide-containing peptides formed by reaction with N-ethylmaleimide [8]. These mechanistic proposals are also consistent with those previously determined for the fragmentation of methionine sulfoxide-containing peptide ions, where the dominant side-chain loss of CH 3 SOH occurs via a charge-remote cis-1,2 elimination reaction under conditions of low proton mobility [14,15].…”
mentioning
confidence: 90%
See 3 more Smart Citations